Discussion on the Solutions to Difficult Problems of DS-Lite Technology Deployed in the Existing Network - Xi Tang; Rong Li; Jianming Yang (Dianxin kexue)
With the rapid development of internet, IPv6 as the next generation internet protocol has been widely concerned. At present, a series of IPv6 experiments have been done, and IPv6 technology has gradually been deployed from laboratory to the application. DS-Lite is recognized as a long-term evolution scheme. The deployment of DS-Lite was carried out, and breakthrough on the key technical difficulties was achieved, such as IT system upgrading, operation process adjustment etc, which may lay the foundation for the IPv6 scale commercial. Aming at the technical difficulties on DS-Lite network deployment, some feasible solutions were put forward.